83.3k views
4 votes
What would the answer for this question be

What would the answer for this question be-example-1
User Trein
by
5.2k points

2 Answers

1 vote


(3x + 2)(4x^(2) - 2x - 7) \\ \: a. = 12 {x}^(3)+ 2x^(2) - 25x - 14

User Daniel Fischer
by
6.5k points
2 votes

Answer:

A

Explanation:

The only one you can eliminate on sight is C. You are going to get an x^3 somewhere along the line.

You can eliminate D on sight as well. The x^3 term is 12x^3 not 7x^3

Doesn't leave much does it?

(3x + 2)(4x^2 - 2x - 7)

3x: 12x^3 - 6x^2 - 21x

2 : 8x^2 - 4x - 14

======================= Add

12x^3 + 2x^2 - 25x - 14

Answer: A

User Kalos
by
5.9k points